2017
DOI: 10.5152/tao.2017.2038
|View full text |Cite
|
Sign up to set email alerts
|

Vidian Canal Types and Dehiscence of the Bony Roof of the Canal: An Anatomical Study

Abstract: Objective: To determine the prevalence of Vidian canal types and dehiscence of the bony roof of the canal. Methods:This study included 594 patients (391 males and 203 females; average age, 32.43±11.98 years; range, 18-65 years). Computed tomography (CT) images were analyzed in terms of the prevalence of Vidian canal types and dehiscence of the bony roof of the canal.Results: Vidian canal types 1, 2, and 3 based on the sphenoid sinus body were found on the right side in 33.8%, 29.7%, and 6.5%, and on the left s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Yegin et al in addition to vidian canal types have also studied the different configurations of the sphenoid sinus floor. 2 They report almost equal incidence of type 1 and type 3 varieties. In addition, they also note a dehiscent vidian canal in nearly one fourth of all scans studied.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Yegin et al in addition to vidian canal types have also studied the different configurations of the sphenoid sinus floor. 2 They report almost equal incidence of type 1 and type 3 varieties. In addition, they also note a dehiscent vidian canal in nearly one fourth of all scans studied.…”
Section: Discussionmentioning
confidence: 98%
“…According to Yegin et al, the incidence of type 1 and type 3 are of almost equal incidence. 2 Kazkayasi et al reported types of vidian canals, notes bilateral protrusion only in half of type 2 configuration. 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of the vidian canal on CT images is important considering the endoscopic sphenoid sinus surgery, the transnasal endoscopic approach of the internal carotid artery, the transnasal endoscopic surgery of the skull base or tumors resulting from the vidian nerve [7,8]. The vidian canal can be dissected and followed during endoscopic endonasal surgery to improve orientation and location of important anatomy [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…The vidian canal is found on the lateral wall of the pterygopalatine fossa. Its anatomical relation with the internal carotid artery makes it a reliable landmark to identify the petrous part of ICA in the endoscopic approach of the skull base surgery 16 . The vidian canal is usually located inferiorly and laterally of the ICA.…”
Section: The Vidian Canalmentioning
confidence: 99%